1997
DOI: 10.1016/s0006-3495(97)78148-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of release of serotonin from isolated secretory granules. I. Amperometric detection of serotonin from electroporated granules

Abstract: We developed a method for measuring the efflux of 5-hydroxytryptamine (5-HT, serotonin) from isolated intact granules of the mast cell of the beige mouse. This method combines electroporation of the vesicle membrane with amperometric detection of 5-HT. A single secretory granule is placed between two platinum electrodes (distance approximately 100 microm) and positioned adjacent (<1 microm) to a carbon fiber microelectrode. A short (approximately 30 micros) high-intensity voltage pulse (electric field of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 26 publications
6
56
0
Order By: Relevance
“…6). These results are consistent with the existence of an intragranular condensed mucin matrix and its subsequent expansion upon exocytosis, as proposed in the ion exchangetriggered phase transition model of granule exocytosis (29,30,68,69).…”
Section: The Vacuolar H ϩ -Atpase Inhibitor Bafilomycin a 1 Increasessupporting
confidence: 90%
“…6). These results are consistent with the existence of an intragranular condensed mucin matrix and its subsequent expansion upon exocytosis, as proposed in the ion exchangetriggered phase transition model of granule exocytosis (29,30,68,69).…”
Section: The Vacuolar H ϩ -Atpase Inhibitor Bafilomycin a 1 Increasessupporting
confidence: 90%
“…Together, these data indicate that the absence of CgA markedly reduces the ability of the vesicular matrix to bind and retain CA, resulting in a shortening of the period for each releasing event. The results obtained also provide direct evidences on the implication of the vesicle matrix in the control of the kinetics of exocytosis (Schroeder et al, 1996;Marszalek et al, 1997;Borges et al, 2000).…”
Section: Discussionmentioning
confidence: 59%
“…Matrix swelling had three major features: (i ) it was massive (i.e., the matrix increased its volume many times); (ii) it had a kinetic similar to the swelling of condensed artificial polymer gels, including a high Hill coefficient; and (iii) it could be arrested to some extent by increasing the extracellular concentrations of Ca 2ϩ and H ϩ , suggesting that these two cations were critical for the mechanism of mucin intragranular condensation. Indeed, it has been shown that the mucin granule lumen is rich in Ca 2ϩ and H ϩ (37,38) In view of these properties, and similar observations in other regulated secretory cell systems (39)(40)(41) 37). Disruption of Ca 2ϩ shielding would result in a rapid increase of repulsive forces among mucin sialic and sulfate groups, and eventually the decondensation and hydration of the granule matrix (14,37).…”
Section: The Matrix Core Paradigmmentioning
confidence: 61%